Investigating toxic aluminium levels in haemodialysis patients after “Day Zero” drought in Cape Town, South Africa - Southon, Bianca; Rusch, Jody A; Vreede, Helena W; Davidson, Bianca; Mweli, Daniel; Wearne, Nicola; Chetty, Malini; Jones, Erika SW (African Journal of Nephrology, 2023)
Introduction: Aluminium is the most abundant metallic element in the earth’s crust and can be consumed through water, medications, and by using metallic cooking utensils. Aluminium levels become a concern when they are above biological exposure limits and can present with multiple clinical complications. When patients have chronic kidney disease and are on haemodialysis, impaired aluminium excretion can lead to its accumulation. Significantly elevated serum aluminium levels were noted in patients with chronic kidney disease (stage 5) on haemodialysis at Groote Schuur Hospital, Cape Town, South Africa. This coincided with one of the worst water crises ever experienced in this metropolitan area, with extreme water restrictions being imposed and alternative water sources being accessed. Method: A multidisciplinary task force performed a systematic evaluation of aluminium concentrations throughout the dialysis water system. Additionally, a thorough investigation was performed to assess the quality of the laboratory results. Results: Possible areas of contamination and potential sources of exposure were excluded. The laboratory results were verified, and potential sources of error were excluded. The investigation verified that aluminium was truly elevated in the serum of patients, and concluded that dialysis was not the cause. Subsequently, patients’ results have declined to baseline, making it possible that there was increased environmental exposure during the drought. Conclusion: This report serves as a reminder to clinicians of acceptable serum aluminium levels in people on dialysis, and in the water system. Furthermore, it highlights the importance of a multidisciplinary collaborative team approach for the investigation of unexpected results or changes in trends.